Four novel genetic mutations are associated with patent foramen ovale in Tibetan population using whole exome sequencing - Li, Hongwei; He, Yongjun; Wu, Yong; Liu, Lanxin; Du, Wei; Wang, Duika; He, Zeng; Zhao, Liming (Frontiers in Genetics, 2025)
ObjectivePatent foramen ovale (PFO), a prevalent congenital cardiac defect, is linked to clinical conditions such as cryptogenic stroke and migraine. The genetic underpinnings of PFO remain poorly elucidated, particularly in Tibet. This study aimed to identify potential pathogenic mutations in Tibetan PFO patients via whole exome sequencing (WES) to clarify its genetic basis.MethodsEighteen Tibetan PFO patients diagnosed by echocardiography were enrolled. Peripheral blood samples underwent WES using Illumina HiSeq platform, followed by bioinformatics analysis to filter rare variants. Pathogenicity was assessed using predictive tools (SIFT, PolyPhen V2, and MutationTaster) and cardiac development-related gene databases (OMIM, HPO, HGMD, and MGI).ResultsIn this study, we identified four novel pathogenetic mutations in Tibetan PFO patients, including GABRP rs201584759 (c.421C>T: p. R141C), GJB4 rs200602523 (c.292C>T: p. R98C), RTTN rs199568901 (c.5410G>A: E1804K), and USH2A rs144768593 (c.5608C>T: p. R1870W). Further analysis indicated that GABRP, GJB4, and RTTN were significantly associated with the occurrence of congenital heart disease.ConclusionThis study first reveals genetic characteristics of Tibetan PFO patients, implicating GABRP, GJB4, RTTN, and USH2A mutations in disrupting cardiac developmental pathways, potentially contributing to the occurrence of PFO. Findings underscore genetic factors regarding PFO prevalence in populations living in high-altitude and provide insights for molecular research and precision medicine.